Efek Regional dan Cardiopulmonary Penggunaan Lidocaine dan Lidocaine-Xylazine pada Blokade Nervus Ischiadicus Domba (REGIONAL AND CARDIOPULMONARY EFFECTS OF LIDOCAINE AND LIDOCAINEXYLAZINE IN SHEEP SCIATIC NERVE BLOCK) - Napitu, Herawati; Noviana, Deni; Soehartono, Raden Harry; Nurhidayat, Nurhidayat (Jurnal Veteriner, 2019)
General anaesthesia has a high risk during surgery, regional anaesthesia with nerve block is expected to minimize the use of general anaesthesia while increase the analgesic effect and muscle relaxation effect. This study aimed to compare the analgesic effects of sciatic nerve block on the hind limb and the effect of lidocaine 2%, and a combination of 2% lidocaine with 2% xylazine on sheep cardiopulmonary function. Sciatic nerve block was guided with ultrasonography and nerve stimulator. In this research, sheep were sedated with diazepam (0.5 mg / kg). Sheep  was divided into three groups; first injected with saline solution (SS), second with lidocaine 2% 5 mg / kg (Lid) and third with lidocaine 2% 5 mg / kg and xylazine 2% 0.1 mg / kg (LidXyl). The results of this research showed that the LidXyl group had the highest analgesic effect and broader blockade area, namely femoris, cruris, and metatarsus-digit. The LidXyl blockade value was highest in the digitmetatarsus region, while the Lid group shows the highest blockade value in the cruris region. The LidXyl group with the addition of xylazine results in a decrease in heart rate and respiration rate. Xylazine increased and extended analgesic effect compared to lidocaine but resulted in a decrease in heart rate and respiration rate in the early minutes of anaesthesia, it is however safe to be used in sheep.